2016
DOI: 10.1186/s13072-016-0064-6
|View full text |Cite
|
Sign up to set email alerts
|

Setdb1-mediated H3K9 methylation is enriched on the inactive X and plays a role in its epigenetic silencing

Abstract: Background The presence of histone 3 lysine 9 (H3K9) methylation on the mouse inactive X chromosome has been controversial over the last 15 years, and the functional role of H3K9 methylation in X chromosome inactivation in any species has remained largely unexplored.ResultsHere we report the first genomic analysis of H3K9 di- and tri-methylation on the inactive X: we find they are enriched at the intergenic, gene poor regions of the inactive X, interspersed between H3K27 tri-methylation domains found in the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 74 publications
1
74
1
Order By: Relevance
“…G9A and GLP1 form a heterodimer and catalyze mono‐ and dimethylation of H3K9 primarily found associated with silent genes in euchromatin (Shinkai and Tachibana, 2011), while SUV39H1 and SUV39H2 are trimethyltransferases responsible primarily for H3K9me3 at centromeric and pericentromeric heterochromatin (Martin and Zhang, 2005). SETDB1 and SETDB2 are H3K9 trimethyltransferases, and while SETDB1 is responsible for methylating endogenous retroviral elements (Liu et al., 2014) and the inactive X chromosome (Keniry et al., 2016), SETDB2 contributes to centromere and pericentromere organization in concert with SUV39H1 (Falandry et al., 2010). Additionally, members of the PRDM family methylate H3K9 and are discussed below.…”
Section: Introductionmentioning
confidence: 99%
“…G9A and GLP1 form a heterodimer and catalyze mono‐ and dimethylation of H3K9 primarily found associated with silent genes in euchromatin (Shinkai and Tachibana, 2011), while SUV39H1 and SUV39H2 are trimethyltransferases responsible primarily for H3K9me3 at centromeric and pericentromeric heterochromatin (Martin and Zhang, 2005). SETDB1 and SETDB2 are H3K9 trimethyltransferases, and while SETDB1 is responsible for methylating endogenous retroviral elements (Liu et al., 2014) and the inactive X chromosome (Keniry et al., 2016), SETDB2 contributes to centromere and pericentromere organization in concert with SUV39H1 (Falandry et al., 2010). Additionally, members of the PRDM family methylate H3K9 and are discussed below.…”
Section: Introductionmentioning
confidence: 99%
“…Xist is the major player in the process of XCI and functions as a scaffold upon which a variety of different proteins act to bring about XCI (17). Proteins associated with the PRC2 complex, the HDAC3 complex (17), and the Setdb1 (18, 19) complex have been proposed to work at the site of Xist localization to efficiently generate stable heterochromatin. Other protein interactions with Xist, such as with YY1, may function to tether Xist to the future Xi (17) or to activate transcription of Xist (23).…”
Section: Dosage Compensation In the Mousementioning
confidence: 99%
“…Our previous mouse genetic screen was successful in identifying epigenetic regulators of transgene variegation (Ashe et al, 2008;Blewitt and Whitelaw, 2013;Blewitt et al, 2005;Chong et al, 2007;Daxinger et al, 2013;Daxinger et al, 2012;Harten et al, 2014;Whitelaw et al, 2010;Youngson et al, 2013). We and others have shown that several of the novel and known epigenetic regulators identified in this screen are also required for XCI, including Smchd1, Setdb1 and Dnmt1 Keniry et al, 2016;Minajigi et al, 2015;Minkovsky et al, 2014;Sado et al, 2000). Given this, we decided to screen the suite of genes that emerged from the mouse genetic screen for roles in XCI using our Xmas ESC system, to try and identify new regulators of XCI.…”
Section: Smarcc1 and Smarca4 Are Required For XCImentioning
confidence: 99%
“…XCI occurs in a stepwise process after being initiated by the upregulation of the long non-coding RNA Xist, which spreads in cis to coat the future Xi (Brockdorff et al, 1991;Brown et al, 1992). Xist then recruits silencing factors (Chu et al, 2015;McHugh et al, 2015;Minajigi et al, 2015) that establish the Xi through the loss of activating (Heard et al, 2001;Keohane et al, 1996;McHugh et al, 2015;Zylicz et al, 2019) and gain of repressive histone marks (Boggs et al, 2002;de Napoles et al, 2004;Fang et al, 2004;Heard et al, 2001;Keniry et al, 2016;Mak et al, 2002;Mermoud et al, 2002;Peters et al, 2002;Plath et al, 2003;Plath et al, 2004;Schoeftner et al, 2006;Silva et al, 2003) and the adoption of a unique bipartite chromosome confirmation (Deng et al, 2015;Giorgetti et al, 2016;Nora et al, 2012;Splinter et al, 2011). Silencing of the Xi is then maintained by DNA methylation (Keohane et al, 1996;Sado et al, 2000), H3K9me3 (Keniry et al, 2016;Minkovsky et al, 2014) and the chromatin regulator Smchd1 Gendrel et al, 2012).…”
Section: Introductionmentioning
confidence: 99%